2021
DOI: 10.1177/20420188211049611
|View full text |Cite
|
Sign up to set email alerts
|

Medullary thyroid carcinoma: recent advances in identification, treatment, and prognosis

Abstract: Medullary thyroid carcinoma (MTC) is a neuroendocrine tumor that represents <5% of all thyroid malignancies and is generally more aggressive than differentiated thyroid cancer. The aim of this study is to provide an update, through review of clinical studies of patients with MTC published between January 1, 2016, and June 1, 2021, on recent advances in the diagnosis and treatment of MTC. This review focuses on updates in biochemical testing, imaging, hereditary disease, surgical management, adjuvant therapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 80 publications
1
12
0
2
Order By: Relevance
“…A further problem, in addition to a more accurate classification, is the lack of specific markers for NEN diagnosis; Chromogranin A (CgA), synaptophysin (Syn), 5-Hydroxyindoleacetic Acid (5-HIAA), neuron-specific enolase (NSE) and cluster of differentiation 56 (CD56) (neural cell adhesion molecule) are currently used for GEP-NENs diagnosis [ 18 , 22 ] and Calcitonin for MTCs [ 23 ]. In GEP-NENs, both Syn and CgA are highly expressed in well-differentiated neoplasms, whereas poorly differentiated carcinomas often maintain synaptophysin positivity while losing CgA expression and acquiring NSE expression [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further problem, in addition to a more accurate classification, is the lack of specific markers for NEN diagnosis; Chromogranin A (CgA), synaptophysin (Syn), 5-Hydroxyindoleacetic Acid (5-HIAA), neuron-specific enolase (NSE) and cluster of differentiation 56 (CD56) (neural cell adhesion molecule) are currently used for GEP-NENs diagnosis [ 18 , 22 ] and Calcitonin for MTCs [ 23 ]. In GEP-NENs, both Syn and CgA are highly expressed in well-differentiated neoplasms, whereas poorly differentiated carcinomas often maintain synaptophysin positivity while losing CgA expression and acquiring NSE expression [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Equally, the prognostic role of 5-HIAA remains controversial [ 26 ]. For MTC diagnosis, calcitonin is a sensitive tumor marker because it correlates with C-cell mass and burden of the neoplasms [ 23 ], but this has also some limitations, such as inter-assay variability, concentration-dependent half-life and rapid degradation [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Targeted therapies are a management option for patients with progressive or symptomatic disease with locoregional or metastatic MTC [ 33 ]. Targeted therapies have helped supplant cytotoxic chemotherapy, which has low efficacy against disease progression, but there is still the problem of toxic side effects and frequent development of tumor resistance when using the current treatment regimen [ 92 ]. These problems indicate that there is still a need to develop an effective treatment for MTC.…”
Section: Systemic Treatmentmentioning
confidence: 99%
“…The registrational phase I/II ARROW trial, with the use of pralsetinib, in patients with MTC demonstrated rapid, potent and durable clinical activity, regardless of RET mutation (NCT03037385) [ 110 ]. These new RET-specific inhibitors have thus far shown a better side effect profile, which is probably due to their high selectivity with VEGFR bypass [ 92 ]. Previous generation of MKIs were not selective and were also blocking the VEGFR factor, part of the angiogenic and proliferative pathways.…”
Section: Systemic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation